Hexokinase 2 promotes ISGylation of Acyl-CoA synthetase long-chain family member 4 in sepsis-induced microglia cells - Guangyang Bai; Shun Ke; Jun Lu; Shanshan Yu; Shusheng Li; Minghao Fang; Jianmin Ling (Journal of Lipid Research)
Metabolic reprogramming is often observed in sepsis-associated microglial cells. However, little is known about the aberrant metabolic genes involved in neuroinflammation and lipid accumulation in microglial cells of sepsis-associated encephalopathy (SAE). Here, we show that hexokinase 2 (HK2) is upregulated and strongly associated with the inflammatory response and lipid metabolism in lipopolysaccharide-induced BV2 cells. Downregulation of HK2 lowered the activation of NOD-like receptor signaling family pyrin domain containing 3, both in BV2 cells and in the hippocampus of cecal ligation and puncture-induced male septic mice. Moreover, the inhibition of HK2 promoted lipid droplet reduction. Mechanistically, HK2 knockdown in microglial cells reduced the ISGylation of Acyl-CoA Synthetase Long-chain Family Member 4 (ACSL4) by interferon-stimulated gene 15 (ISG15). Notably, siISG15 effectively down-regulated the expression of ACSL4 in lipopolysaccharide-induced BV2 cells. Our findings provide new mechanistic insights into HK2 in microglial cells through regulation of ACSL4 ISGylation, suggesting a promising therapeutic strategy for treating SAE by targeting HK2. Our findings suggest that HK2 modulates ISGylation of ACSL4 in sepsis-induced microglial cells, indicating that therapeutic targeting of HK2 may constitute a promising strategy for SAE.